Процесс инкорпорации крымскотатарской знати в состав российского дворянства - Сичаева, Г.А. (Культура народов Причерноморья, 2013)
В данной статье будет сделана попытка осветить процесс вхождения крымскотатарских беев и мурз в высшее сословие Российской империи – дворянство. Данный процесс имел свои особенности, что определяет задачи тематики данного исследования. У даній статті буде зроблена спроба висвітлити процес входження кримськотатарських беїв і мурз в вищий стан Російської імперії – дворянство. Даний процес мав свої особливості, що визначає завдання тематики даного дослідження. In this article attempt to cover process of occurrence krymean tatars beys and murzs in the highest estate of the Russian Empire – the nobility will be made. This process had the features that defines problems of scope of this research. With completion of annexation of the Crimea, the difficult and painful period of largescale reforms and transformations in the won territory deterioration of position of the population of the Crimea and absolute economic decline of edge became which result began. In structure of the Russian nobility and it socially – economic and policy – a legal status the features had process of incorporation of the krymskotatarsky nobility. It should be noted that this process isn't an exception for the Crimean region, for all the XVIII century the Russian government carried out a number of similar measures for the attitude towards all representatives of the highest estates of local population in the won territories.